PENGARUH SUASANA TOKO DAN KEBERAGAMAN PRODUK TERHADAP KEPUTUSAN PEMBELIAN PADA PM COLLECTION PEKANBARU - Natasha Ardiyanti; Mandataris Mandataris (Politeknik Bisnis Indonesia, 2024)
The research is aimed at finding out the influence of store atmosphere and product diversity on purchasing decisions at PM Collection Pekanbaru. The development of the business world is increasingly rapid, marked by the increasing number and complexity of challenges that exist within it. One of the many businesses is the fashion business. The independent variables are store atmosphere and product diversity, while the dependent variable is purchasing decisions. The method used in the research was quantitative methods using the SPSS version 20 program. The sample used was 99 respondents using the Accidental Sampling technique for PM Collection Pekanbaru consumers. The data source used in the research are primary and secondary data. The results of this research are that store atmosphere (X1) has a positive and significant influence on purchasing decisions (Y), product diversity (X2) has a positive and significant influence on purchasing decisions (Y), and store atmosphere and product diversity have a significant influence on purchasing decisions.